Development of Carbon Monoxide detecting device using MQ-7 sensor along with its statistical analysis - Ferdousi, Jahan Ara; Ananto, Samiul Ehsan; Ahmed, Md. Naveed (BRAC University, 2014)
This thesis report submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.